PENGETAHUAN TENTANG TUHAN DALAM TEKS SERAT SASTRA GENDHING - Werdiningsih, Yuli Kurniati; Andrian, Setia Naka (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: IN; mso-bidi-language: AR-SA;" lang="IN">This study aims to describe the knowledge of God in the text of Serat Sastra Gendhing.<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">This research is a qualitative type. The source of the research data is <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: IN; mso-bidi-language: AR-SA;" lang="IN">Serat Sastra Gendhing<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN"> text editing. The research data are words, phrases, clauses, and sentences that contain knowledge about God in the text of <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: IN; mso-bidi-language: AR-SA;" lang="IN">Serat Sastra Gendhing<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">. Data is collected through a classification process; identification; inventory. Data were analyzed by hermeneutic studies through methods of reduction, interpretation, and conclusions. The results of research in the form of knowledge about God contained in the text of <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: IN; mso-bidi-language: AR-SA;" lang="IN">Serat Sastra Gendhing<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN"> as follows. God is in rasa, God is known in the union between rasa and pangrasa, knowledge of God involves all aspects of human beings. Knowledge about God is not only reflected in worship, but also in the rasa, pikiran, and perbuatan that implement the attributes of God<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; color: #222222; mso-ansi-language: IN; mso-fareast-language: IN; mso-bidi-language: AR-SA;" lang="IN">.